Penerapan Teknik Tiupan (Mangenet dan Manganak-anaki) Sulim Batak Toba dalam Lagu Manopoti Dosa di Gereja Kristen Protestan Indonesia (GKPI) Pagar Beringin. Skripsi, Jurusan Pendidikan Musik Gerejawi Institut Agama Kristen Negeri Tarutung. - Rade Anjani Siahaan; Roy J.M Hutagalung; Eben Haezarni Telaumbanua Lince Rauli Ture Simamora (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the application of the mangenet and manganak-anaki blowing techniques in Batak Toba sulim performance on Hymn No. 27, “Meski Tak Layak Diriku” (“Though I Am Not Worthy”), and to explain their roles and functions in shaping musical quality, the worship atmosphere, and the congregation’s theological appreciation at GKPI Pagar Beringin Church. This research employs a qualitative approach with a descriptive method. Data were collected through direct observation during worship services, interviews with sulim players, church ministers, and congregation members, as well as documentation in the form of audio-visual recordings of sulim performances. The results show that the mangenet technique is applied to sustained notes, particularly at the ends of musical phrases, in order to maintain sound continuity, clarify musical structure, and create a calm and reflective atmosphere. Meanwhile, the manganak-anaki technique functions as a melodic ornament on connecting tones within phrases, enriching musical expression without altering the original melody of the hymn. Both techniques contribute to producing a soft sulim tone that blends with congregational singing and does not dominate the musical texture. In the context of worship, the use of these techniques helps build a solemn atmosphere and supports the congregation in internalizing the theological meaning of the hymn, which emphasizes humility and surrender before God. This study also reveals an integration of Batak Toba cultural elements into church liturgical practice, where the sulim serves as a contextual medium for expressing faith. Thus, the mangenet and manganak-anaki techniques serve not only as technical aspects of sulim performance but also play an important role in enhancing the musical quality of worship and deepening the spiritual experience of the congregation.